Research on Crop Water Status Monitoring and Diagnosis by Terahertz Imaging - LI, BIN; Wang, Rong; Ma, Jianjun; Xu, Weihao (Frontiers in Physics, 2020)
Leaf water content is regarded as an important index of crop health in agriculture. It is in great need to develop a rapid, non-destructive and accurate diagnose method which can measure and assess water level of different types of crops. In this research, winter wheat leaves were selected and the reliability and applicability of THz imaging technique for destructive and non-destructive water content monitoring were studied. Based on the measurement of THz transmission, smaller water loss in distal regions of a winter wheat leaf is shown when compared with that in basal regions during the natural dehydration process. A high correlation between the gravimetric water status level and THz transmission is observed during dehydration and after rehydration. The results show that the transmission of THz waves can be used to evaluate the water content of winter wheat leaves by destructive and non-destructive geometries, which suggests that THz imaging can be a good potential tool to measure the water content to diagnosis crop health in agriculture in a rapid, non-destructive and accurate way.